SISTEM PENGAMBILAN KEPUTUSAN PENERIMAAN KARYAWAN DI PT.BBIP (BUKIT BARISAN INDAH PERMAI) ) MENGGUNAKAN METODE PROFILE MACHING - Yeni Nurjani (JURNAL AKADEMIKA)
Growing information technology as it is today, it is encouraging the emergence of information technology devices it is often associated with the development of computers that the more days undergoing significant change, resulting in an information system. One way to build a system of hiri ng decision makers at PT. BBIP using the Profile Matching. At the PT. BBIP, recruitment still manually with the assessment of the applicant's done one by one, so it takes a long time to make decisions. With the development of the information technology world, it is necessary to program applications that are localized for determining the assessment in decision making recruitment so as to provide time efficiency and effectiveness in selecting applicants at PT. BBIP. This study was developed in PT. BBIP Jambi. This system dikembang the programming language Visual Basic 6.0 and database Ms. Access as for data input is applicant data, assessment data, the data gap, the data weighting and data perangkingan. The input data will be processed and produce output reports applicant data and report the results of assessment of applicants that can be used to determine applicants who deserved to be an employee at PT. BBIP